Analisis Kesantunan Berbahasa pada Naskah Ketoprak Kembang Katresnan Karya Bondan Nusantara serta Relevansinya sebagai Bahan Ajar Bahasa Jawa Tingkat SMA - Galuh Sekar Arumsari; Atikah Anindyarini; Rahmat Rahmat (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2022)
This research of pragmatic study is the politeness inside ketoprak script. In this pragmatic study the researcher aims to identify language politeness in ketoprak script Kembang Katresnan by Bondan Nusantara and the relevancy as javanes material teaching in senior high school. This research is deskriptif kualitatif research. The data obtained with data document analyse and interview. Validity of data using source triangulation and theory triangulation. The result from this research is find speech in ketoprak script Kembang Katrensna by Bondan Nusantara according to musly in language politeness with Chaer (2010: 11).  Script can changed according to the level of leangunge of variety Javanes to class XII Senior High School level according to KD 3.1 is to identify, understand, and analyse of oral language using in all situasion according to the manners.